Comparative genomic analysis of multiple strains of two unusual plant pathogens: Pseudomonas corrugata and Pseudomonas mediterranea - Trantas, Emmanouil A.; Licciardello, Grazia; Almeida, Nalvo F.; Witek, Kamil; Strano, Cinzia P.; Duxbury, Zane; Ververidis, Filippos; Goumas, Dimitrios E.; Jones, Jonathan D.; Guttman, David S.; Catara, Vittoria; Sarris, Panagotis F. (Frontiers in Microbiology, 2015)
The non-fluorescent pseudomonads, Pseudomonas corrugata (Pcor) and P. mediterranea (Pmed), are closely related species that cause pith necrosis, a disease of tomato that causes severe crop losses. However, they also show strong antagonistic effects against economically important pathogens, demonstrating their potential for utilization as biological control agents. In addition, their metabolic versatility makes them attractive for the production of commercial biomolecules and bioremediation. An extensive comparative genomics study is required to dissect the mechanisms that Pcor and Pmed employ to cause disease, prevent disease caused by other pathogens, and to mine their genomes for commercially significant chemical pathways. Here, we present the draft genomes of nine Pcor and Pmed strains from different geographical locations. This analysis covered significant genetic heterogeneity and allowed in-depth genomic comparison. All examined strains were able to trigger symptoms in tomato plants but not all induced a hypersensitive-like response in Nicotiana benthamiana. Genome-mining revealed the absence of a type III secretion system and of known type III effectors from all examined Pcor and Pmed strains. The lack of a type III secretion system appears to be unique among the plant pathogenic pseudomonads. Several gene clusters coding for type VI secretion system were detected in all genomes.